2018
DOI: 10.14701/ahbps.2018.22.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Management of residual gall bladder: A 15-year experience from a north Indian tertiary care centre

Abstract: Backgrounds/AimsA residual gallbladder (RGB) following a partial/subtotal cholecystectomy may cause symptoms that require its removal. We present our large study regarding the problem of a RGB over a 15 year period.MethodsThis study involved a retrospective analysis of patients managed for symptomatic RGB from January 2000 to December 2015.ResultsA RGB was observed in 93 patients, who had a median age of 45 (25–70) years, and were comprised of 69 (74.2%) females. The most common presentation was recurrence pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 27 publications
3
49
0
Order By: Relevance
“…11 With increasing availability and use of high resolution axial imaging modalities such as computed tomography and magnetic resonance imaging, it is increasingly recognized that these symptoms may be attributable to a remnant gallbladder. In two case series presented by Singh et al 7 and Concors et al, 8 diagnosis of the remnant gall bladder is often challenging. Furthermore, Singh et al identified that reporting and disclosure of a subtotal cholecystectomy was absent 71% of these cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 With increasing availability and use of high resolution axial imaging modalities such as computed tomography and magnetic resonance imaging, it is increasingly recognized that these symptoms may be attributable to a remnant gallbladder. In two case series presented by Singh et al 7 and Concors et al, 8 diagnosis of the remnant gall bladder is often challenging. Furthermore, Singh et al identified that reporting and disclosure of a subtotal cholecystectomy was absent 71% of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Singh et al identified that reporting and disclosure of a subtotal cholecystectomy was absent 71% of these cases. 7 Both of these case series place particular weight on imaging, computed tomography and magnetic resonance imaging, to confirm the existence of the remnant and to define the anatomy prior to proceeding. In our patient cohort, the incidence of repeat cholecystectomy is 0.25%, for the period of 1998-2016.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations